2015
DOI: 10.1002/2014jc010254
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual oxygen variability on the Washington and Oregon continental shelves

Abstract: The coastal waters of the northern portion of the California Current System experience a seasonal decline in oxygen concentrations and hypoxia over the summer upwelling season that results in negative impacts on habitat for many organisms. Using a regional model extending from 43 N to 50 N, with an oxygen component developed in this study, drivers of seasonal and regional oxygen variability are identified. The model includes two pools of detritus, which was an essential addition in order to achieve good agreem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 92 publications
6
75
0
Order By: Relevance
“…Thus, high concentrations of mycosporine-like amino acid compounds released from senescing cells during storm events may have been trapped as foam along the Washington shoreline. By contrast, because the Oregon coastline is relatively less retentive (Siedlecki et al 2015), neither foam nor unusually high carcass deposition were observed along northern Oregon beaches despite the presence of the A. sanguinea bloom. Retentive systems, including Monterey Bay (Ryan et al 2008), may be particularly prone to this specific etiology of HAB impact.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus, high concentrations of mycosporine-like amino acid compounds released from senescing cells during storm events may have been trapped as foam along the Washington shoreline. By contrast, because the Oregon coastline is relatively less retentive (Siedlecki et al 2015), neither foam nor unusually high carcass deposition were observed along northern Oregon beaches despite the presence of the A. sanguinea bloom. Retentive systems, including Monterey Bay (Ryan et al 2008), may be particularly prone to this specific etiology of HAB impact.…”
Section: Discussionmentioning
confidence: 78%
“…5B) and that the bloom was also present along the coastline of Oregon (Du et al 2011), but did not result in elevated rates of carcass deposition there. Although the Washington coastline is not considered a retentive system, the wide shelf, the relatively weak upwelling winds and the frequent presence of the plume from the Columbia River along the coast north of the river mouth during storms (Hickey & Banas 2008) likely result in this region retaining particles, including HABs, for longer periods than, by comparison, the Oregon coast (Siedlecki et al 2015). Thus, high concentrations of mycosporine-like amino acid compounds released from senescing cells during storm events may have been trapped as foam along the Washington shoreline.…”
Section: Discussionmentioning
confidence: 99%
“…Using a similar configuration to the one used in the present study on the Namibian OMZ, Gutknecht et al (2013a) observed that the differences between the simulated OMZ volume and CARS increased towards the shelf, which could be related to the exclusion of the DO demand from the sediments in the model. The role of benthic processes in constraining the DO demand has been studied in the northern California current system (Bianucci et al, 2012;Siedlecki et al, 2015), indicating that locally such processes might be essential to explain the hypoxic conditions. The inclusion of a sediment module in the current model setting is planned for future work to address this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Giddings et al (2014) also describes validation against moored, ship-based, and satellite observations of water properties and currents for the years 2004Ð2007. Biogeochemical validation for the same years is provided by Davis et al (2014) and Siedlecki et al (2015).…”
Section: Oceanographic Datamentioning
confidence: 99%